Overexpression of Hevea brasiliensis HbICE1 Enhances Cold Tolerance in Arabidopsis - Yuan, Hong-Mei; Sheng, Ying; Chen, Wei-Jie; Lu, Yu-Qing; Tang, Xiao; Ou-Yang, Mo; Huang, Xi (Frontiers in Plant Science, 2017)
Rubber trees (Hevea brasiliensis) were successfully introduced to south China in the 1950s on a large-scale; however, due to the climate, are prone to cold injury during the winter season. Increased cold tolerance is therefore an important goal, yet the mechanism underlying rubber tree responses to cold stress remains unclear. This study carried out functional characterization of HbICE1 (Inducer of CBF Expression 1) from H. brasiliensis. A nucleic protein with typical features of ICEs, HbICE1 was able to bind to MYC recognition sites and had strong transactivation activity. HbICE1 was constitutively expressed in all tested tissues, with highest levels in the bark, and was up-regulated when subjected to various stresses including cold, dehydration, salinity and wounding. When overexpressed in Arabidopsis, 35S::HbICE1 plants showed enhanced cold resistance with increased proline content, reduced malondialdehyde (MDA) metabolism and electrolyte leakage, and decreased reactive oxygen species (ROS) accumulation. Expression of the cold responsive genes (COR15A, COR47, RD29A, and KIN1) was also significantly promoted in 35S::HbICE1 compared to wild-type plants under cold stress. Differentially expressed genes (DEGs) analysis showed that cold treatment changed genes expression profiles involved in many biological processes and phytohormones perception and transduction. Ethylene, JA, ABA, as well as ICE-CBF signaling pathways might work synergistically to cope with cold tolerance in rubber tree. Taken together, these findings suggest that HbICE1 is a member of the ICE gene family and a positive regulator of cold tolerance in H. brasiliensis.